2011
DOI: 10.1152/advan.00010.2011
|View full text |Cite
|
Sign up to set email alerts
|

The sensory modality used for learning affects grades

Abstract: Second-year undergraduated students from 2008, 2009, and 2010 cohorts were asked to respond a questionnaire to determine their learning style preferences, the VARK questionnaire (where V is visual, A is aural, R is reading-writing, and K is kinesthetic), which was translated into Spanish by the author. The translated questionnaire was tested for wording comprehension before its application in the actual study. Using the results of the VARK questionnaire, students were classified as unimodal or multimodal and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 15 publications
(23 reference statements)
3
19
1
1
Order By: Relevance
“…In terms of the learning style that showed a low academic achievement, the findings of this research is in line with the research by Moayyeri (2015) with the visual learning style acquiring the lowest achievement as compared to other learning styles. However, the result is different from the finding of Ramirez (2011) who found that the aural learning style showed the lowest academic achievement.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In terms of the learning style that showed a low academic achievement, the findings of this research is in line with the research by Moayyeri (2015) with the visual learning style acquiring the lowest achievement as compared to other learning styles. However, the result is different from the finding of Ramirez (2011) who found that the aural learning style showed the lowest academic achievement.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, there no significant differences between the mean of students who adopted other learning styles. This research finding is in line with the research done by Ramirez (2011) andMoayyeri (2015) who found that students who adopted the unimodal read-write learning styles achieved significantly better as compared to those who adopted other learning styles. In the study by Ramirez (2011) two types of test questions, namely objective questions and arithmetic questions, were given to the students with different learning styles.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Chile: Three cohorts (2008,2009, and 2010) of second-year undergraduate medicine and sport science students, Universidad de Santiago de Chile, Santiago, Chile participated in this study. Usage of MCQs showed no significant differences however when arithmetic questions were given to solve, unimodal R students performed the best [17]. 6.…”
Section: Modality -Style/ Preference/ Strengthmentioning
confidence: 84%